2020
DOI: 10.1186/s13722-020-00185-8
|View full text |Cite
|
Sign up to set email alerts
|

Guided web-based treatment program for reducing cannabis use: a randomized controlled trial

Abstract: Background: The aim of this study was to investigate the effects of a web-based treatment program with therapist guidance for adults and adolescents with regular cannabis use from the general population. Methods:A double blinded randomized controlled trial with a parallel group design was conducted (intervention group n = 151, wait-list control group n = 152). Follow-up 12 weeks from treatment commencement of a 13-module intervention. The primary outcome was frequency of cannabis use. Time by group interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(51 citation statements)
references
References 33 publications
0
51
0
Order By: Relevance
“…Users of the therapist-led intervention had greater decrease in alcohol consumption at 3 months compared to the control, although other time by group effects were not significant (38). The trial targeting regular cannabis use (N = 303) compared a guided self-help intervention with a waitlist control (WLC) in a ratio of (1:1), showing no significant time by group effects on cannabis use at the 3-month followup, yet such effects were revealed in the subset of participants that had not sought other professional help during the trial (39). In both trials, all participants were asked to rate their attitudes toward internet interventions (see full description of measure below) before entering the program, of which n = 1,037 + 256 participants answered the form, implying a coverage rate of 89% and 84% in the alcohol and cannabis program, respectively.…”
Section: Methods Sample and Proceduresmentioning
confidence: 98%
See 1 more Smart Citation
“…Users of the therapist-led intervention had greater decrease in alcohol consumption at 3 months compared to the control, although other time by group effects were not significant (38). The trial targeting regular cannabis use (N = 303) compared a guided self-help intervention with a waitlist control (WLC) in a ratio of (1:1), showing no significant time by group effects on cannabis use at the 3-month followup, yet such effects were revealed in the subset of participants that had not sought other professional help during the trial (39). In both trials, all participants were asked to rate their attitudes toward internet interventions (see full description of measure below) before entering the program, of which n = 1,037 + 256 participants answered the form, implying a coverage rate of 89% and 84% in the alcohol and cannabis program, respectively.…”
Section: Methods Sample and Proceduresmentioning
confidence: 98%
“…This study is a secondary analysis of data from two randomized controlled trials of internet interventions for harmful alcohol use or dependence (38) and regular cannabis use (39), respectively. See each respective publication for details on participant recruitment, procedure, treatments and full outcomes reporting.…”
Section: Methods Sample and Proceduresmentioning
confidence: 99%
“…Notably, while smartphone apps are promising, the review by Colbert et al [ 9 ] shows that current evidence for apps targeting unhealthy alcohol use is still limited compared with available evidence for internet-based interventions. Focusing on cannabis use among adults and adolescents, Sinadinovic et al [ 10 ] showed that a web-based treatment program with therapist guidance was not superior to a waiting list design, although subgroup analyses showed that the intervention may be beneficial for some.…”
Section: Special Issue Themesmentioning
confidence: 99%
“…An encouraging example is Lundqvist and Ericsson’s ‘Cannabis Cessation Program’ (CCP, Nordic abbreviation: HAP), developed in the 1990s, which has spread and is currently used in many Swedish municipalities [ 7 , 8 ]. The model has mainly been used as an individual-based intervention [ 9 ], but it has also been tested in a group format and in online formats [ 10 – 12 ].…”
Section: Introductionmentioning
confidence: 99%